A role of annealing temperature on the properties of lanthanum oxide (La2O3) microplates by reflux routes. (2020) - Karthikeyan, S.; Selvapandiyan, M.; Shanavas, S.; Anbarasan, P.M.; Acevedo, R.
Abstract: The morphology controlled the synthesis of La2 O3 is important for their application in the fields of semiconductors. In this work nanostructured La2 O3 has been synthesized by reflux method using lanthanum nitrate, urea and double distilled water as starting materials. The approximate band gap of the as-prepared and calcined samples was calculated from the absorption spectrum are 5.8 and 5.9 eV respectively. The as-prepared and calcined products were characterized by X-ray diffraction (XRD), Scanning electron microscopy (SEM), Fourier transform infrared (FT-IR), Bandgap was calculated by UV–visible spectroscopy.